Dirāsah Tahlīliyah Limanhaj Kitāb Ta’lim Allughah Al’arabiah Lilshafi Al ūla Altsanawī Biwizārah Alsyu`ūn Aldīniyah Al Indūnīsiyah ām 2020 alā Daw' Kitāb Ida'āt Limu’alimī Allughah Al’arabiah Lighayri Alnātiqīn Bihā - Musdalifa; Kristiana (Mauriduna: Journal of Islamic Studies, 2022)
This study aims to know the extent of the good curriculum standard in the Arabic language teaching book of the Indonesian Ministry of Religious Affairs in 2020 for the first secondary grade by referring to the book “Idoat Limuallimil Luqoh Al-Arabiyyah Li Goiri An-Natiqiina Biha", which is in this book to raise the professional competence of the teacher in teaching Arabic to non-native speakers. And this study adopts the descriptive-analytical approach with a qualitative approach, and the study proved that in the curriculum of the educational book of the Indonesian Ministry of Religious Affairs in 2020 for the first secondary grade, it most agreed with the extent of the curriculum mentioned in the book “Illuminations for Teachers of Arabic Language for Non-Native Speakers” as one of the objectives of teaching The Arabic language, teaching its elements, skills, language training, language tests, and methods of teaching. The percentage of this analysis is 66.89%, so the textbook "Illuminations for Teachers of Arabic for Non-Native Speakers" agreed. Penelitian ini bertujuan untuk mengetahui sejauh mana standar kurikulum yang baik pada buku ajar bahasa Arab Kementerian Agama RI Tahun 2020 untuk kelas I SMA dengan mengacu pada buku “Idoat Limuallimil Luqoh Al-Arabiyyah Li Goiri An-Natiqiina Biha” , yang ada dalam buku ini untuk meningkatkan kompetensi profesional guru dalam mengajar bahasa Arab kepada non-penutur asli. Dan penelitian ini mengikuti pendekatan deskriptif-analitis dengan pendekatan kualitatif, dan penelitian tersebut membuktikan bahwa dalam kurikulum Kementerian Negara Republik Indonesia. Buku Pendidikan Agama Tahun 2020 untuk kelas 1 Madrasah Aliyah ini, paling setuju dengan luasnya kurikulum yang disebutkan dalam buku “Pencerahan Bagi Guru Bahasa Arab Bagi Penutur Asli” sebagai salah satu tujuan pengajaran Bahasa Arab, mengajarkan unsur-unsurnya, keterampilan, pelatihan bahasa, tes bahasa, dan metode pengajaran. Dan prosentase analisis ini adalah 66,89%, sehingga buku pendidikan tersebut setuju dengan buku “Pencerahan Bagi Guru Bahasa Arab Bagi Non-Native Speakers”.